Concentrating solar systems: Life Cycle Assessment (LCA) and environmental issues. (October 2017) - Lamnatou, Chr.; Chemisana, D.
Abstract: The present article is a critical literature review about studies which are based on LCA (life cycle assessment) and about studies which include environmental issues about concentrating solar systems (concentrating photovoltaic (CPV), concentrating solar power (CSP), etc.). The results reveal that CPV environmental profile depends on several factors such as the materials of the concentrator and the direct solar radiation. On the other hand, there are different factors which influence CSP profile (from environmental point of view), including water use and materials e.g. for storage. By considering the literature review presented it can be noted that: 1) Regarding CPV, there is a need for more studies which investigate different concentration ratios, CPVT (concentrating photovoltaic/thermal) systems, low-concentration CPV, strategies to reduce the impact of certain components such as the tracking (especially for large-scale applications) and the concentrators, 2) Concerning CSP, there is a need for more investigations about dish-Stirling, storage materials, strategies for water savings, soiling effect, 3) In general, regarding concentrating solar systems, there is a need for more studies with Fresnel lenses and reflectors, for small-scale systems for buildings and for multiple final applications (desalination, drying, etc.), 4) With respect to the adopted methods/environmental indicators, certainly CO2.eq emissions, embodied energy and EPBT (energy payback time) can provide useful information for concentrating solar systems; nevertheless, there is a need for utilization of additional methods (e.g. based on midpoint, endpoint approaches) which can also offer useful information.